MO290CLINICAL DIFFERENCES AND OUTCOMES IN ANCA ASSOCIATED VASCULITIS PATIENTS ACCORDING TO SEROLOGICAL PHENOTYPE – EXPERIENCE FROM CROATIAN REFERRAL CENTER. (29th May 2021) - Crnogorac, Matija; Horvatić, Ivica; Kacinari, Patricia; Tišljar, Miroslav; Brechelmacher, Ana; Senjug, Petar; Galešić Ljubanović, Danica; Galesic, Kresimir
Abstract: Background and Aims: ANCA associated vasculitis (AAV) are usually classified according to clinical presentation (Chapel-Hill consensus conference). There is however suggestion by some authors that AAVs could be classified according to ANCA specificity. We aimed to compare AAV patients in our cohort according to serological phenotype. Method: This study included 106 consecutive AAV patients with renal involvement in the period from 2007-2017. We performed renal biopsy on patients using automatic 16 Gauge needle. Light, immunofluorescent and electronic microscopy were performed. Category variables were analysed with Fisher Exact testom and continuous with Kruskal-Wallis testom. Statistical difference was then analysed posthoc with Chi-square test. Primary outcomes were combined outcome progression to end-stage renal disease, defined as persistent (more than three months) need for renal replacement therapy or permanent reduction of EGFR to <15ml/minute (according to CKD EPI formula) and/or death (ESRDD), death (D) and ESRD alone, and disease relapse. Kaplan Meyer survival analysis and multivariate Cox proportional hazard regression analysis were used to explore difference between phenotypes and finding significant predictors regarding outcomes. Results: The study included 106 AAV patients with renal involvement: 66 (61, 1%) MPA, 20 (18, 5%) GPA, 20 (18, 5%) RLV. There were 14 (13%) PR3-ANCA positive patients, 57 (52, 8%) MPO ANCA positive, 5 (4, 6%) PR3-ANCA+MPO-ANCA and 32 (29, 6%) ANCA negative patients. Average SCr was 316, 5 μmol/l (IQR 207, 0-548, 5), 24-hour proteinuria median was 1, 7g/24h (IQR 0, 8-2, 8). Clinicaly PR3 positive AAVs had significantly more ENT (p<0, 001) and skin (p=0, 001) involvement, and ANCA negatives had significantly less lung involvement (p<0, 001), and less expressed constitutional symptom (p=0, 031). Interestingly both MPO and PR3 positive AAV patients had approximately equal percentage of lung involvement. Both PR3 (p=0, 021) and MPO (p=0, 009) positive AAVs had higher BVAS score compared to ANCA negatives, while on average there was no significant difference between MPO, PR3 and double positives. PR3 (p=0, 007) and MPO (p=0, 003) positive AAVs had higher CRP levels than ANCA negatives, and PR3 AAVs had on average higher CRP than MPO AAVs though not statistically significant. There was strong tendency (p=0, 087) to PR3 AAVs having more acute tubular damage than other groups and also strong tendency (p=0, 092) of having more crescentic formations than MPO AAVs and ANCA negatives but similar to double positives. Though it was not statistically significant ANCA negatives had higher median of IFTA compared to other groups. PR3 AAVs and double positives required significantly more often treatment with PLEX (p=0, 042) and dialysis (p=0, 04) compared to MPO positive AAVs and ANCA negatives. We then grouped patients into ANCA positives and ANCA negatives. ANCA negative patients were younger (p=0, 02), expressed clinicaly more as RLV (p<0, 001). BVAS score was lower in ANCA negative group (p= 0, 003). ANCA positive patients presented more often with RPGN (p=0, 027) and ANCA negatives with nephrotic syndrome. There was tendency of ANCA positives being treated with PLEX more often (p=0, 074). In the primary outcome analysis there were no statistically significant differences between serological phenotypes though for relapse rate (p=0, 155) curve dynamics through follow up time seems to show higher relapse rate for PR3 and double positive AAVs after 2 years of follow up. Conclusion: Serological classification of AAVs is an interesting way for overcoming the limitations of clinical classification. Apart from differences between MPO, PR3 and double positive AAVs, it appears there are even more significant differences between ANCA positive and negative ones.